Fabrication and Applications of Multi-Fluidic Electrospinning Multi-Structure Hollow and Core–Shell Nanofibers. (June 2022) - Li, Dianming; Yue, Guichu; Li, Shuai; Liu, Jing; Li, Huaike; Gao, Yuan; Liu, Jingchong; Hou, Lanlan; Liu, Xiaofeng; Cui, Zhimin; Wang, Nü; Bai, Jie; et al.
Abstract: Recently, electrospinning (ESP) has been widely used as a synthetic technology to prepare nanofibers with unique properties from various raw materials. The applications of functionalized nanofibers have gradually developed into one of the most exciting topics in the field of materials science. In this review, we focus on the preparation of multi-structure fibrous nanomaterials by means of multi-fluidic ESP and review the applications of multi-structure nanofibers in energy, catalysis, and biology. First, the working principle and process of ESP are introduced; then, we demonstrate how the microfluidic concept is combined with the ESP technique to the multi-fluidic ESP technique. Subsequently, the applications of multi-structure nanofibers in energy (Li + /Na + batteries and Li–S batteries), hetero-catalysis, and biology (drug delivery and tissue engineering) are introduced. Finally, challenges and future directions in this emerging field are summarized.